ANALISIS KELAYAKAN USAHA PADA UMKM SEKTOR MINUMAN KEKINIAN ”TUMBAS TEH SUSU” JEMBER - Muhammad Hanip; Adil Kristianto; Alfin Dwi Yulianto; Adelia Kusuma Ningrum; Meynisa Aulia Khoirurizka; Destha Bunga Nanda; , Fatihatur Rizqiyah; Aza Citra Khodijah Gg; Salsa Nabila Julia Putranti; Ruwanda Oktavia Andini; Tasya Nur Imaniyah; Oryza Ardhiarisca; Avisenna Harkat (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the feasibility of the “Tumbas Teh Susu” beverage business in Jember Regency based on financial and non-financial aspects. The research employs a qualitative descriptive approach, with data collection techniques including observation, in-depth interviews, and documentation. The analysis encompasses legal, market, financial, technical, management, socio-economic, and environmental aspects. The non-financial analysis results indicate that the business possesses strong market prospects among students, a strategic location, and efficient production processes. However, improvements in formal legal licensing are still required. Financially, the business is highly feasible, indicated by a Net Present Value (NPV) of Rp91.388.420, a Profitability Index (PI) of 10.14, and a Payback Period (PP) of less than 3 months. Overall, the “Tumbas Teh Susu” business is declared feasible to operate and has strong potential for sustainable development.